Physical Fitness Test Performance Probability with Increasing Age: Suggestions for Practical Applications in Military Physical Training [Probabilidade de Desempenho No Teste de Aptidão Física E O Aumento Da Idade: Sugestões de Aplicações Práticas No Treinamento Físico Militar] - Aedo-Munoz, E (Universidade Federal de Santa Catarina, 2020)
This article analyzes the Physical Fitness Test (PFT) which is performed by the Brazilian Navy to check the physical parameters of its military members in order to present the performance of probabilities with increasing age. We analyzed 702 PFT data in this study, separated into three groups based on the age of those assessed by the PFT, as follows: young adults (YA, n=91, age range between 20-30 years), adults (A, n=243, age range between 30-40 years) and mature adults (MA, n=368, age range between 40-50 years old). PFT measurements were: Body Mass Index (BMI), 100 m freestyle swimming, 3,200 m running, 1 min sit-ups, Pull-up on the bar and Push-up test.The main results indicated significant differences between groups when compared Body mass (YA: 79.1±11.4kg and A: 82.1±14kg < MA: 84.1±12.3kg), BMI (YA: 25.4±2.9 <A: 26.4±4.3 <MA: 27.5±4),Pull-ups (YA: 10.8±4.6 freq./min <A: 10±3.6 freq./min <MA: 8.5±4.7 freq./min), 3,200 m running time (YA: 1282,1±172,4s <A: 1421±199.8s <MA: 1566.7±192.4s) and 100 m swimming time (YA: 760.0 ± 56.6s <A: 800.0 ± 118.2s <MA: 882.0 ± 113.7s) and the regression analysis demonstrated that 3,200 m running and pull-ups were the most affected variable of aging process (p<0.05). In summary, it is possible to carry out a practical application, considering aging process and the decline of the aerobic capacity and the upper limbs strength-power in Military Physical Training. © 2020, Universidade Federal de Santa Catarina. All rights reserved.